Accessibility in digital games: Combining interaction techniques for improved experience of users with motor impairments - Margarida Nazaré Pereira dos Santos (2024)
The gaming industry has been focusing on accessibility features more and more as the years pass by, focused on a more inclusive society and searching for expanding the number and diversity of gamers. However, there is still a lot of work to be done in order to make games completely accessible. Accessibility technologies could, in theory, substitute the need for using the hands with dexterity to play a game. However, in a game that needs more than one action at once, using only one of the technologies, as most studies report, would prove futile and overly complicated. With this study, we aimed to expand the research of accessibility in video games, specifically for people with motor disabilities that have some type of incapacity in the usage of the hands. We aimed to study how the integration of two technologies compares to the use of only one (complemented by traditional input methods), and hypothesize that the implementation will prove more immersive and fun to play, as well as be more accessible. With a preliminary interview, we gathered insight into disabled users' issues and what they think about the effort being made to accommodate them. In the game we used for the research, a top-down 3D shooter, there are two main actions: movement and shooting. Our integrated system consists of a nose tracker and a gaze tracker, linked to different actions in the game. The nose tracker is used for the movement action while the gaze tracker is used for the shooting action. The individual systems use, each, one of these technologies and the keyboard, a traditional input method, for the complementing action. Following the implementation of the two technologies individually, we tested them against the original input devices to understand how the technologies performed when compared to the original experience. Through a second phase of user tests, we tested the integration of these two technologies against their individual implementation. Our results indicate that users did not prefer the combination of technologies over their individual use. However, they liked the experience with the gaze tracker, finding it fun and enjoyable, and accessible enough, provided you had movement in one hand.